The social educator as manager of self- managed communities towards a didactics of group work - Carlos G. Juliao Vargas (Corporación Universitaria Minuto de Dios, 2005)
This paper seeks to reflect upon the function of social educators as promoters of self-managing communities as well as to outline the didactic contribution which group work techniques provide for this task. Therefore, the competencies that a social educator should have been addressed from a trace concept of "community" and its relationship whit social education as a non formal process; principally insisting on its role as "leader" of the self-management community processes: how far Leadership should go and where it should stop. It can be concluded that the social educator is required to work among groups of human beings with the main purpose of arousing the collective processes of teaching and learning of knowledge, attitudes and strategies. These strategies lead communities to manage the environment in which they live in an autonomous way so that decent living conditions are guaranteed for everyone.